Dis/Trust and data-driven technologies - David Duenas-Cid; Stefano Calzati (Internet Policy Review, 2023)
This concept paper contextualises, defines, and systematises the concepts of trust and distrust (and their interrelations), providing a critical review of existing literature so as to identify gaps, disjuncture, and continuities in the use of these concepts across the social sciences and in the context of the consolidation of the digital society. Firstly, the development of the concept of trust is explored by looking at its use in different disciplines -e.g. sociology, psychology, law, and management- and then confronted with that of distrust, often regarded-somewhat simplistically-as its opposite. Secondly, the review invites a reflection on the suitability of current definitions of trust and distrust when applied to the implementation of current data-driven technologies (dis/trust in technology) and their workings (dis/trust through technology). The discussion is relevant and timely, not only given the renewed interest in finding the touchpoints between dis/trust and digital-related issues but also to provide a benchmarking overview on this topic, which is still lacking in current literature.
Keywords: 300; Trust; Distrust; Technology; Data-driven technology; Data